Transforming children’s knowledge and perception of sharks through a serious game - Costa, M.; Machado Alexandre, I.; Boaventura, D.; Santana, P. (Journal of Computers in Education, 2026)
Due to the alarming decline in shark populations caused by overfishing and unsustainable practices, raising public awareness about this environmental crisis has become crucial. In response, an educational game was developed with the goal of shifting children’s negative perceptions of sharks. The game includes two mini-games designed to educate young players about the important role sharks play in maintaining marine ecosystem health. Through interactive activities, the game helps children understand the challenges sharks face as a result of human impact. The mini-games were created to be both educational and engaging, using adaptive mechanisms to tailor the experience to the unique characteristics of each player. This adaptive design allowed for an analysis of how different player profiles interacted with the game, assessing whether the data collected revealed consistent patterns or notable differences across profiles. The developed game contributes to the field of educational games aimed at conservation by encouraging positive attitude shifts towards sharks. Tests conducted with 38 children, aged 9 to 11, revealed a significant increase in their knowledge about sharks and a more positive perception of these animals as a result of playing the game. Furthermore, the game successfully adapted to different player profiles, enabling all participants, regardless of age, gender, or skill level, to intuitively complete the tasks. The study underscores the potential of educational games to inspire more responsible and sustainable behaviors in ocean conservation.